"DUALISME PENYELESIAN SENGKETA PERBANKAN SYARIAH (Pasca Putusan Mahkamah Konstitusi Nomor 93/PUU-X/2012) " - Triana Sofiani (Jurnal Hukum Islam, 2015)
This study aims at exploring the issues of dualism in solving sharia- bankingproblems, which was resolved through constitutional court's judicial decision number 93/PUU-X/2012. This decision provided explanation that was based on article 55 act (2) Law Number 21 Year 2008 about Sharia Banking which does not have legal bounding power. After the judicial decision, it turned out that there were many judicial problems when solving sharia-banking problems through non-litigation bodies, especially through National Sharia Arbitrary Agency (Badan Arbitrase Syariah Nasional/Basyarnas). Instead of this, each Basarnas' decision should be registered to district court and the execution of Basyarnas decisions should be implemented in accordance with the instructions given by district court, instead of religious court, which actually is the only body with absolute power to solve problems within the area of Sharia Economic finance and Sharia Banking.